Low-Temperature Chemical Vapor Deposition Growth of MoS2 Nanodots and Their Raman and Photoluminescence Profiles - Mawlong, Larionette P. L.; Biroju, Ravi K.; Giri, P. K. (Frontiers in Nanotechnology, 2021)
We report on the growth of an ordered array of MoS2 nanodots (lateral sizes in the range of ~100-250 nm) by a thermal chemical vapour deposition (CVD) method directly onto SiO2 substrates at a very low substrate temperature (510-560 °C). The temperature dependent growth and evolution of MoS2 nanodots, and the local environment of sulfur induced structural defects and impurities were systematically investigated by the field emission scanning electron microscopy, micro-Raman and X-ray photoelectron spectroscopy (XPS) techniques. At the substrate temperature of 560°C, we observed mostly few layer MoS2, and at 510°C multilayer MoS2 growth, as confirmed from the Raman line shape analysis. With reduced substrate temperature, the density of MoS2 nanodots decreases and layer thickness increases. Raman studies show characteristics Raman modes of crystalline MoS2 layer, along with two new Raman modes centred at ~346 and ~361 cm-1, which are associated with MoO2 and MoO3 phases, respectively. Room temperature photoluminescence (PL) studies revealed strong visible PL from MoS2 layers, which is strongly blue shifted from the bulk MoS2 flakes. The strong visible emission centred at ~ 658 nm signifies free excitonic transition in the direct gap of single layer MoS2. Position dependent PL profiles shows excellent uniformity of the MoS2 layers for samples grown at 540 and 560°C. These results are significant for the low temperature CVD growth of a few layer MoS2 nanodots with direct band gap photoluminescence on a flexible substrate.